Lack of additional effects of long‐term, low‐dose clarithromycin combined treatment compared with topical steroids alone for chronic rhinosinusitis in China: a randomized, controlled trial. Issue 1 (30th November 2017) - Deng, Jie; Chen, Fenghong; Lai, YinYan; Luo, Qing; Xu, Rui; Ou, Chunquan; Fu, Qingling; Shi, Jianbo
Abstract : Background: In China, clarithromycin is considered an effective treatment option for chronic rhinosinusitis (CRS) due to its unique immunopathologic characteristics. Our study's aim was to determine whether a topical steroid and clarithromycin combination is better than a single topical steroid for Chinese patients with CRS. Methods: Patients with CRS with/without nasal polyps were included in this study and randomly assigned to a clarithromycin plus budesonide aqua nasal spray group (CLM + BUD, clarithromycin 0.25 g/d and budesonide 256 μg/d) or a budesonide‐alone group (BUD, budesonide 256 μg/d). The treatment period was 3 months. The primary outcome was visual analog scale (VAS) score for 5 major symptoms and a general nasal symptom. Other assessments included the 22‐item Sino‐Nasal Outcome Test (SNOT‐22), computed tomography scan (Lund‐Mackay score), and rigid nasal endoscopy (Lund‐Kennedy score). Nasal secretion evaluation was the secondary outcome. Results: Seventy‐four patients were included and randomly assigned to the CLM + BUD group (n = 38) or the BUD group (n = 36). VAS scores for nasal obstruction, rhinorrhea, smell reduction, headache, nasal pain, and general nasal symptom were markedly improved in both treatment arms, but the differences between groups were not significant. Furthermore, SNOT‐22, Lund‐Mackay, and Lund‐Kennedy scores improved significantly after treatment in both groups, and were slightly better in the CLM + BUD group. For the responders in the CLM + BUD group, interleukin (IL)‐6 and IL‐8 were markedly reduced. Conclusion: The combination of CLM + BUD for the treatment of first‐time‐diagnosed CRS in this Chinese population cohort did not show a better effect compared with a single BUD regimen, but it may have a better effect in some patients with increased IL‐6 or IL‐8.